2017
DOI: 10.1097/mph.0000000000000767
|View full text |Cite
|
Sign up to set email alerts
|

T2* Magnetic Resonance Imaging Study of Pancreatic Iron Overload and its Relation With the Diabetic State in Thalassemic Patients

Abstract: The present study was performed to evaluate pancreatic hemosiderosis by means of magnetic resonance imaging (MRI) T2* and its relation to the diabetic state in thalassemic patients. One hundred thirty transfusion-dependent thalassemic patients from Zafar adult thalassemia clinic, Tehran, Iran, were enrolled in the study. Data such as age, type of thalassemia, age at diagnosis, transfusion duration, ferritin level, and fasting blood sugar results were gathered. Pancreatic MRI T2* was performed for all patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…However, in our study and that of ElAlfy et al [16], a statistically significant difference was shown in renal T2* time between the healthy control group and beta-thalassemia patients. There was no significant association between age and renal T2* time in our study, which is consistent with the literature [16,22].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, in our study and that of ElAlfy et al [16], a statistically significant difference was shown in renal T2* time between the healthy control group and beta-thalassemia patients. There was no significant association between age and renal T2* time in our study, which is consistent with the literature [16,22].…”
Section: Discussionsupporting
confidence: 93%
“…ElAlfy et al [16] showed a weak correlation between renal R2* time and LIC value and a moderate negative correlation with cardiac T2* time. Hashemieh et al [22] showed a weak correlation between renal T2* time and liver and also cardiac T2* time. While Hashemieh et al revealed a weak correlation between ferritin and renal T2* time, ElAlfy et al [16] could not find any correlation at all.…”
Section: Discussionmentioning
confidence: 97%
“…Both echogenicity and glandular size reduction were significantly associated with transfusion treatment time. 28,29 The findings of the present study demonstrated that in this cohort, there was a weak association between pancreatic head size and serum ferritin levels. This may provide some lower-level evidence that patients with higher serum ferritin levels may have an enlarged pancreatic head.…”
Section: Discussionmentioning
confidence: 44%
“…22 Nonetheless, studies have yielded contradictory findings with regard to the link between pancreatic T2* or R2* value and glucose metabolism. [23][24][25][26][27][28] Some studies supported the usefulness of pancreatic T2* or R2* value for the identification of patients with glucose dysregulation, 23,24,26 whereas others did not report such correlation. 25,27,28 Intense periductal lymphoplasmacytic infiltration with interstitial fibrosis is the primary characteristic of autoimmune pancreatitis (a type of chronic pancreatitis), leading to mass-like swelling of the pancreas.…”
Section: Relaxation Timesmentioning
confidence: 99%